Neuropathological lesions in cetaceans found stranded from1991 to 1993 on the coasts of Italy. - Di Guardo G.; CORRADI, Attilio; Agrimi U.; Zizzo N.; Morelli L.; Perillo A.; Kramer L. H.; CABASSI, Enrico; Kennedy S. (1995)
Detailed anatomo-histopathological and immunohistochemical investigations were carried out on the brain tissue of 37 cetaceans (31 striped dolphins, 4 bottle-nosed dolphins, 1 fin-whale, and 1 minke whale), found stranded from 1991 to 1993 on the cost of Latium, (8 subjects), Tuscany (8 sibjects), and Apulia (21 subjects). Frequently encountered lesions included malacia (36.7%), often occouring as leukoencephalomalacia, haemmorage (27%), and encephalitis (32.4%), which in 3 cases (8.1%) was caused by Toxoplasma and in 9 cases (24.3%) had a viral aetiology. Viral encephalitis was observed in 8 striped dolphins (Stenella coeruloalba) and in an adult minke whale (Balenoptera acutorostrata). The latter was seropositive to Morbillivirus. Morbillivirus-specific antigens were demonstrated by immunohistochemistry in the brain tissueof 6 of the above striped dolphins, 3 of which were found stranded on the cost of Apulia, 1 on the cost of Latium, and 2 on the cost of Tuscany. Finally, an additional interesting finding was represented by the coexistence, in 2 striped dolphins, of a morbillivirus and Toxoplasma encephalitis.